Ribozyme-mediated attenuation of pancreatic beta-cell glucokinase expression in transgenic mice results in impaired glucose-induced insulin secretion. - Efrat, S (1994)
Phosphorylation of glucose to glucose 6-phosphate by glucokinase (GK; EC 2.7.1.2) serves as a glucose-sensing mechanism for regulating insulin secretion in beta cells. Recent findings of heterozygous GK gene mutations in patients with maturity-onset diabetes of the young (MODY), a form of type II (non-insulin-dependent) diabetes characterized by autosomal dominant inheritance, have raised the possibility that a decrease in beta-cell GK activity may impair the insulin secretory response of these cells to glucose. To generate an animal model for MODY we have expressed in transgenic mice a GK antisense RNA with a ribozyme element under control of the insulin promoter. Mice in two independent lineages had about 30% of the normal islet GK activity. Insulin release in response to glucose from in situ-perfused pancreas was impaired; however, the plasma glucose and insulin levels of the mice remained normal. These mice are likely to be predisposed to type II diabetes and may manifest increased susceptibility to genetic and environmental diabetogenic factors. They provide an animal model for studying the interaction of such factors with the reduced islet GK activity.